(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
In this paper, we embark on a cultural-genealogical journey to trace the concept of time, observing the shifts in the concept of time in Western culture. Time concerns religions, science, philosophy, and cultural creation. The perception of time in any culture also dictates the form of thought within that culture. At the basis of Western culture is a linear concept of time that has its origins in Biblical texts, while in Eastern cultures, the concept of time is circular. The genealogical research in this paper examines the roots of the linear concept of time in Western culture and the fundamental changes that this concept has undergone over the generations amid processes of secularization, the growth of capitalism, and the penetration of digital technology. Today, we inhabit the seam between two technologies, one mechanical and the other virtual and digital. These shifts force us to examine our shifting cultural reality through many different lenses, including concerning our perceptions of time. Although our cultural inquiry about future changes in our perception of time in virtual spaces is only just beginning, it has already raised quite a few questions that we address here.